Identification of Occupational Accidents at PTPN IV Air Batu, Kisaran Using Job Safety Analysis and Hazard and Operability Methods - Sofyan, Diana Khairani; Amri; Purnawan, Reza Adrian (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2026)
Workplace accidents remain a critical concern in the palm oil processing industry, which is characterized by complex operations and high-risk activities, particularly in key operational areas such as sterilizers, clarification units, boilers, screw presses, and sand trap tanks. This study aims to identify potential hazards and assess the level of occupational accident risk at PT Perkebunan Nusantara IV Unit Air Batu using a combined approach of Job Safety Analysis (JSA) and Hazard and Operability Study (HAZOP). Data were collected through field observations, questionnaires, and accident reports recorded between 2023 and 2024. The findings indicate that the primary causes of workplace accidents stem from technical equipment failures, unsafe working environments, and non-compliance with standard operating procedures. The highest risk levels were identified at the boiler and sterilizer stations, with risk scores reaching 20–25, categorized as extreme hazard zones. Dominant hazards include exposure to high-temperature steam and hot oil, pressure leakage, musculoskeletal injuries from manual handling, and gas exposure in confined spaces. Recommended corrective actions involve strengthening engineering controls through the installation of interlock systems and automated sensors, developing risk-based standard operating procedures, enforcing appropriate personal protective equipment (PPE) usage, and implementing regular safety training and evaluation. The integration of JSA and HAZOP methods proved effective in providing a comprehensive risk mapping framework and can serve as a strategic reference for enhancing occupational health and safety (OHS) management systems in the palm oil industry.